Occurrence and potential transmission of extended-spectrum beta-lactamase-producing extraintestinal pathogenic and enteropathogenic Escherichia coli in domestic dog faeces from Minnesota - Johnson, Timothy J; Armstrong, Joseph R; Johnston, Brian; Merino-Velasco, Irene; Jamborova, Ivana; Singer, Randall S; Johnson, James R; Bender, Jeff B (Zoonoses and public health, 2022)
Interactions between humans and pets are increasingly valued in western countries, leading to more extensive contact between humans and their pets within households. Although the magnitude of the risk of transfer of Escherichia coli between humans and their companion animals is undefined, that such transmission occurs has been established and warrants attention. This study examined 186 fresh faecal samples from companion dogs visiting 22 municipal dog parks in the Minneapolis/Saint Paul metropolitan area, Minnesota, USA. Samples were processed to isolate 3rd-generation cephalosporin-resistant E. coli, which were further characterized using PCR-based virulence genotyping, antimicrobial susceptibility profiling and whole-genome sequencing. Of the 186 faecal samples, 29% yielded cephalosporin-resistant E. coli, and 2.2% yielded extended-spectrum beta-lactamase producers. Co-resistance to sulfonamides was typical (77.3% of isolates), and multidrug resistance (i.e. to ≥3 antimicrobial classes), including to combinations of tetracyclines, phenicols, quinolones and aminoglycosides, was substantial (18.9% of isolates). Identified beta-lactamase genes included blaCMY-2 , blaTEM-1B , blaTEM-1 , blaCTX-M-24 , blaCTX-M-15 and blaOXA-1 . Genome sequencing of 14 isolates identified genes typical of extraintestinal pathogenic E. coli or enteropathogenic E. coli. In three instances, closely related isolates were recovered from different dogs, within either the same park-suggesting transfer of E. coli between dogs within the park-or different parks-suggesting that dogs may be pre-disposed to carry certain E. coli types, such as those from serogroups O4, O71 and O157. This study adds to the existing evidence that companion dogs can harbour and share antimicrobial-resistant E. coli with presumed intestinal or extraintestinal pathogenic potential.
Keywords: psi; sulfonamidy; Escherichia coli Infections; Tetracyclines; faecal; Feces; Sulfonamides; Escherichia coli; aminoglykosidy; tetracykliny; Cephalosporins; beta-laktamasy; antibakteriální látky; Minnesota; lidé; beta-Lactamases; enteropatogenní Escherichia coli; Dog Diseases; feces; domácí zvířata; canine; cephalosporin; Dogs; cefalosporiny; Pets; Anti-Bacterial Agents; Animals; infekce vyvolané Escherichia coli; Enteropathogenic Escherichia coli; Humans; Quinolones; nemoci psů; chinolony; Aminoglycosides; zvířata